2011
DOI: 10.1021/jp2075644
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of One-Step Solid-State Reaction for Li4Ti5O12/C

Abstract: The kinetics of one-step solid-state reaction of Li(4)Ti(5)O(12)/C in a dynamic nitrogen atmosphere was first studied by means of thermogravimetric-differential thermal analysis technique at five different heating rates. According to the double equal-double steps method, the Li(4)Ti(5)O(12)/C solid-state reaction mechanism could be properly described as the Jander equation, which was a three-dimensional diffusion with spherical symmetry, and the reaction mechanism functions were listed as follows: f(α) = (3)/(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Additionally, the authors applied the developed neural network to the experimental data for Li 4 Ti 5 O 12 /C high-temperature reaction. The ANN output agrees well with the literature results [ 100 ] of these data analysis accomplished with isoconversional and model-fitting kinetic approaches. It is noteworthy that according to the isoconversional analysis, the activation energy of the process is more or less constant throughout the reaction, thus, indicating the single-step reaction kinetics.…”
Section: Thermokinetic Analysis With Neural Networksupporting
confidence: 86%
“…Additionally, the authors applied the developed neural network to the experimental data for Li 4 Ti 5 O 12 /C high-temperature reaction. The ANN output agrees well with the literature results [ 100 ] of these data analysis accomplished with isoconversional and model-fitting kinetic approaches. It is noteworthy that according to the isoconversional analysis, the activation energy of the process is more or less constant throughout the reaction, thus, indicating the single-step reaction kinetics.…”
Section: Thermokinetic Analysis With Neural Networksupporting
confidence: 86%
“…Different strategies have been used to overcome LTO drawbacks, essentially focusing on the kinetic limitations. Downsizing LTO particles and modifying their morphology increase the available exchange surface and improve the Li + insertion kinetics, and coating LTO particles with a conductive carbonaceous layer, combined with nanostructuration, shows significant improvements. The doping of the LTO structure by substituting either Li + /Ti 4+ cations (Mg 2+ , Ca 2+ , Zn 2+ , Cr 3+ , Al 3+ , La 3+ , Zr 4+ , V 5+ , Nb 5+ , Ta 5+ , Mo 6+ , etc.) or O 2– anions (Br – , N – , Cl – , or F – ) is another strategy pursued to improve its electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…They found that three dimensional diffusion model (D3) was the most probable mechanism function for the reaction. Hu et al [39] also investigated the kinetics of solid state reaction for Li 4 Ti 5 O 12 /C and observed Jander D3 as the most probable mechanism and the average value of activation energy for the system was 278 kJ/mol using FWO and FRL (Friedman-Reich-Levi) method. sintering method in the previous reports [6], which is most probably due to its low bulk density and porosity.…”
Section: Determination Of Thermodynamic Parametersmentioning
confidence: 99%